Development of a professional ethics code universal model for Internet marketing organisations - R. A. Glaz; E. F. Shamaeva (Вестник университета)
The terms and definitions involved in the research paper have been analysed and divided into two semantic groups. A historical reference on the history of ethics formation as a science has been given. On its basis the current state of ethics and its problems have been formed. The main trends in the Internet advertising market have been analysed, as a result of which the main directions of development in the sphere and the problems arising from this have been determined. A semantic and structural analysis of the existing ethical codes of related fields has been carried out. As a result, existing shortcomings have been revealed. Based on the work done, a template has been proposed, which in the future can serve as a basis for creating similar models in other areas.